Comparative transcriptomic analysis reveals the cold acclimation during chilling stress in sensitive and resistant passion fruit (Passiflora edulis) cultivars - Wu, Yanyan; Huang, Weihua; Tian, Qinglan; Liu, Jieyun; Xia, Xiuzhong; Yang, Xinghai; Mou, Haifei (PeerJ, 2021)
Chilling stress (CS) is an important limiting factor for the growth and development of passion fruit (Passiflora edulis) in winter in South China. However, little is known about how the passion fruit responds and adapts to CS. In this study, we performed transcriptome sequencing of cold-susceptible cultivar Huangjinguo (HJG) and cold-tolerant cultivar Tainong 1 (TN1) under normal temperature (NT) and CS conditions, and a total of 47,353 unigenes were obtained by seven databases. Using differentially expressed unigenes (DEGs) analysis, 3,248 and 4,340 DEGs were identified at two stages, respectively. The Gene Ontology (GO) enrichment analysis showed that the DEGs were mainly related to phosphorylation, membrane protein, and catalytic activity. In Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, the unigenes of plant-pathogen interaction, plant hormone signal transduction and fatty acid metabolism were enriched. Then, the 12,471 filtered unigenes were clustered into eight co-expression modules, and two modules were correlated with CS. In this two modules, 32 hub unigenes were obtained. Furthermore, the unigenes related to CS were validated using quantitative real-time PCR (RT-qPCR). This work showed that the expression levels of CS-related unigenes were very different in two passion fruit cultivars. The results provide information for the development of passion fruit with increased chilling tolerance.
Keywords: Passion fruit; Chilling stres; RNA-seq; WGCNA; Hub genes; RT-qPCR